Phytoremediation of selected heavy metals using Bryophyllum daigremontianum (Raym-Hamet & H. Perrier) A. Berger (Bangladesh Journal of Botany, 2020)
Heavy metals are hazardous to plants as well as to humans. The purpose of the current work was to explore the phytoextraction potential of B. daigremontianum (Raym.-Hamet & H. Perrier) A. Berger for the uptake of cadmium (Cd), nickel (Ni) and zinc (Zn) through roots, leaves and stem. B. daigremontianum grown in the contaminated soil showed relatively higher values for the uptake of Cd, Ni and Zn as compared to those grown in control soil. However, the accumulation rate of heavy metals was arranged in the order: Zn, Ni and Cd in root > leaf > stem. There was a significant difference at p < 0.05 from their relevant control. Bioconcentration factors (BCF root) values clearly show the differences of heavy metals in control and contaminated plants which were 1.0106, 0.8306 and 0.6652, indicating the uptake in the order Zn > Ni > Cd. B. daigremontianum used for the Phytostabilization of Zn because the BCF value of the plant for this metal is greater than one.